Edward Troy and the witch cat - "Sargent, Sarah, 1937-"; "McCully, Emily Arnold." (Chicago)
Relates the experiences of Edward Troy the spring and summer he is 9 years old.
Keywords: CATS -- FICTION.;FRIENDSHIP -- FICTION.;CITY AND TOWN LIFE -- FICTION.;AFRICAN AMERICANS -- FICTION